(untitled) (Bangladesh Journal of Medical Science, 2016)
Introduction: Inflammation of the lacrimal sac, dacryocystitis is one of the important causes of ocular morbidity in Indian subcontinent. Objective: To isolate and identify the aerobic bacterial pathogens associated with dacryocystitis and to determine their antibacterial sensitivity pattern. Materials and methods: A total of 304 individuals were included in the study. Blocked tissue / pus was collected and microbial analysis was done. Results: Infection rate was more in the female than male, statistically highly significant (p<0.0001). The culture positivity was 91% (277/304), infection rate was maximum at the age of 40-50 years 200/204, 98% (p<0.0001). In culture positive cases gram positive cocci is commonly isolated. Most of gram positive bacteria are sensitive to Chloramphenicol. Gram negative bacteria were sensitive to Gentamycin, Chloramphenicol and Ciprofloxacin. Conclusion: Knowledge of the bacteriology of dacryocystitis and the susceptibility of the bacteria towards antibiotics helped the needy for proper treatment, so that time as well as money can be saved. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.399-402